Analysis of the wetting and exothermic properties of preoxidized coal and the microscopic mechanism. (15th May 2023) - Pan, Rongkun; Hu, Daimin; Han, Xuefeng; Chao, Jiangkun; Jia, Hailin
Abstract: In the processes of coal mining and transportation, low-temperature oxidation occurs continuously, and it is accompanied by multiple wetting. The effect of water on coal spontaneous combustion (CSC) cannot be ignored. To study the wetting and exothermic properties of preoxidized coal and the mechanism of its effect on CSC, molecular dynamics simulations, microcalorimetry, scanning electron microscopy (SEM) and fourier transform infrared spectrometer (FTIR) are used to analyze the molecular dynamics mechanism, heat of wetting (Hw ), surface structure and microscopic group changes. Experimental results show that the surface potential distribution of coal is uneven, which leads to the adsorption of polar water molecules; the total energy of the system continues to decrease during the adsorption process. The preoxidation treatment further develops pore fissures, increases the percentage of hydrophilic groups and evaporates the original water. Therefore, in the coal low-temperature oxidation stage, the higher the degree of preoxidation is, the greater the Hw value. After preoxidation and wetting, the loose and porous characteristics of coal are further reflected; the oxygen percolation and adsorption are enhanced, which accelerates the system heat accumulation and thus intensifies the risk of CSC. The experimental results provide an important theoretical basis for the prevention of CSC. Highlights: The influence mechanism of coal preoxidation degree on wettability is analyzed. As coal preoxidation deepens, the heat of wetting increases. Preoxidation, wetting and drying promote pores and fissures development in coal. The main ways that water promotes coal spontaneous combustion are discussed.